Differences in ambulatory care fragmentation between cancer survivors and noncancer controls. Issue 13 (14th April 2020) - Pinheiro, Laura C.; Reshetnyak, Evgeniya; Safford, Monika M.; Nanus, David; Kern, Lisa M.
Abstract : Background: Patients with chronic conditions are treated by many providers, which can increase the risk of communication gaps across providers and potential harm to patients. However, to the authors' knowledge, the extent of fragmented care among this population is unknown. In the current study, the authors sought to determine whether cancer survivors have more fragmented care than noncancer controls and to quantify the extent of fragmentation. Methods: Data from the REasons for Geographic And Racial Differences in Stroke (REGARDS) study linked to Medicare claims were used. The authors included beneficiaries with continuous Part A and B coverage for 12 months at the time of their baseline REGARDS survey. The primary outcome of the current study was claims‐based fragmentation over 12 months, which was calculated using the reversed Bice‐Boxerman Index so a higher score reflected greater fragmentation. Unadjusted differences in fragmentation were compared between cancer survivors and controls. Beta regression models were used to estimate associations between cancer status and fragmentation, adjusting for potential confounders. Results: The authors included 4922 participants aged ≥65 years at baseline. Of these patients, approximately 21% were cancer survivors. Survivors had a median of 11 visits (interquartile range, 7‐15 visits) with 5 providers compared with controls, who had a median of 9 visits (interquartile range, 6‐14 visits) with 4 providers ( P  < .0001). Cancer survivors had significantly more fragmented care compared with controls (median reversed Bice‐Boxerman Index, 0.80 vs 0.76; P  < .0001). After adjusting for confounders, cancer survivors had an increased odds of having fragmented care (odds ratio, 1.08; 95% CI, 1.02‐1.14). Conclusions: Care fragmentation is more prevalent among cancer survivors compared with those without a history of cancer. Future studies should examine whether fragmentation puts survivors at risk of worse outcomes. Abstract : Even 2 or more years after the conclusion of cancer treatment, fragmented health care continues to be more prevalent among individuals with a history of cancer than those without. Understanding when individuals with a history of cancer are at greatest risk of fragmentation and how this may relate to cancer and noncancer outcomes can inform clinicians regarding if and when they should consider intervening to reduce fragmentation as a way to potentially improve patient outcomes.